1989
DOI: 10.3171/jns.1989.70.2.0271
|View full text |Cite
|
Sign up to set email alerts
|

Intrasellar persistent trigeminal artery associated with a pituitary adenoma

Abstract: The case of a patient with Cushing's disease and a pituitary macroadenoma, who also had a persistent trigeminal artery coursing through the sella turcica on preoperative imaging studies, is presented. The patient was treated by transsphenoidal resection of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…PTA variants are uncommon (2) and are reported to have an incidence of approximately 0.18% (73). In relation to the dorsum sellae, approximately 50 to 59% of all cases of PTA penetrate the sella turcica, course along their own groove, perforate the dura near the clivus, and then join the basilar artery with thinning of the sellar floor and abnormalities of the dorsum sellae being a frequent finding while in the remaining 41 to 50% of cases, the PTA runs lateral to the sella turcica (39,52). In 1993, Ohshiro et al (52) reviewed the relation of PTA to the dorsum sellae in 22 of 25 autopsy cases described up to the time of their writing.…”
Section: Saltzman Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…PTA variants are uncommon (2) and are reported to have an incidence of approximately 0.18% (73). In relation to the dorsum sellae, approximately 50 to 59% of all cases of PTA penetrate the sella turcica, course along their own groove, perforate the dura near the clivus, and then join the basilar artery with thinning of the sellar floor and abnormalities of the dorsum sellae being a frequent finding while in the remaining 41 to 50% of cases, the PTA runs lateral to the sella turcica (39,52). In 1993, Ohshiro et al (52) reviewed the relation of PTA to the dorsum sellae in 22 of 25 autopsy cases described up to the time of their writing.…”
Section: Saltzman Classificationmentioning
confidence: 99%
“…About one century elapsed until the artery was angiographically demonstrated for the first time by Sutton in an article published in the British Journal of Radiology in 1950 (75). Persistent trigeminal artery (PTA) is the most common of the primitive carotid-basilar anastomoses that persist into adulthood, with an estimated incidence of 0.1 to 1.0% on cerebral angiograms (17,20,36,39,47,52,67,70). A number of cases of PTA and its variants found at autopsy (21,30, 34,52,60,67,70,82), on cerebral angiograms (2,6,7,17,27, 35,73,85), and on MRI and MRA scans (7,18,63) demonstrate the anatomy (30,39,52,67) of this primitive anastomosis and its relationship to various vascular diseases (1,16,19,20,25,30,36,44,47).…”
Section: Introductionmentioning
confidence: 99%
“…Four cases of functional macro-adenoma and one case of non-functional adenoma accompanying PPTA have been reported in the literature [6][7][8][9]. PPTA and accompanying prolactinoma is an extremely rare condition and previously only one case has been reported in the English literature [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although patients are usually asymptomatic, it has been reported that it may accompany third and sixth cranial nerve palsies, aneurysms, vascular anomalies and hemifacial spasm [2][3][4]. The pituitary lesions accompanying PPTA and trigeminal neuralgia (TN) associated with a PPTA are rarely seen [5][6][7][8][9][10]. Knowledge of the typical imaging findings of PPTA prevents major surgical complications [8].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are only five reported cases of association between PTA and concomitant pituitary adenoma (8)(9)(10)(11)(12).…”
Section: Sumáriomentioning
confidence: 99%